Extrusion of Femtosecond Laser-Implanted Intrastromal Corneal Ring Segments in Keratoconic Eyes: Prevalence, Risk Factors, and Clinical Outcomes - Amr Mounir; Mahmoud Mohamed Farouk; Marwa Mahmoud Abdellah; Engy Mohamed Mostafa (Journal of Ophthalmology)
Purpose. To evaluate the prevalence, possible risk factors, and clinical results of femtosecond laser implanted intrastromal corneal ring segment (ICRS) extrusion in keratoconic eyes. Patients and Methods. This is a retrospective observational study evaluating 333 eyes of 269 patients who were subjected to femtosecond laser-implanted Keraring ICRS in the Sohag Refractive Center, Sohag, Egypt, from January 2014 to January 2019. The study included eyes with channels created by a femtosecond laser (60 kHz IntraLase femtosecond system; Advanced Medical Optics, Santa Ana, California, USA) with implantation of Keraring intrastromal corneal ring segments (Mediphacos, Belo Horizonte, Brazil). Patient data and causes of Keraring extrusions were identified as being those rings that migrated or showed melting of the cornea with no other reason which required segment removal. Results. Seven eyes were found to fit the criteria of ring extrusion (2.1%) out of the 333 eyes which had Keraring implantation. All extruded rings were from patients with keratoconus grade 3, with eccentric cones, and with femtosecond creation of the tunnel. Four eyes belonging to 3 patients (57.1%) had a history of vernal Keratoconjunctivitis, yet they did not show signs of activity at the time of implantation. They reported excessive rubbing just before they presented with conjunctival hyperemia and foreign body sensation. Five eyes (71.4%) showed chronic sun exposure. The mean minimal corneal thickness was 401.85 μm (range 384–420 μm), while the mean maximum keratometry was 61 D (range 55.18–68.96 D). Most of the extruded rings had large arcs. Six eyes had crosslinking (CXL) at the same session of the Keraring implantation. The simultaneous CXL treatment is considered as a possible significant risk factor for ring extrusion. Conclusion. ICRS is an effective reversible option for patients with keratoconus who are intolerant to hard contact lenses, yet the choice of cases and ring segments is mandatory for satisfactory results. Moreover, meticulous history taking and examination reduces the incidence of complications including extrusion.